Manajemen Kampanye Humas BKKBN Melalui Program Gerakan Ayah Teladan Indonesia (Gati) Dalam Meningkatkan Kesadaran Peran Ayah - Siti Miftakhurrohmah; Yanto Yanto; Maryaningsih Maryaningsih (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the public relations campaign management conducted by the National Population and Family Planning Agency (BKKBN) of Bengkulu Province through the Gerakan Ayah Teladan Indonesia (GATI) program in increasing fathers’ awareness of their role in child parenting. This research is motivated by the low involvement of fathers in parenting, which is influenced by patriarchal culture and the perception that childcare is primarily the mother’s responsibility. The study used a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, and documentation with informants selected using purposive sampling, consisting of individuals directly involved in the implementation of the GATI program at BKKBN Bengkulu Province. Data analysis employed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The results show that the public relations campaign management of the GATI program was implemented through four stages based on the theory of Cutlip, Center, and Broom: defining, planning, taking action and communicating, and evaluating. In the defining stage, BKKBN identified the low awareness of fathers’ roles as the main issue. The planning stage involved designing communication strategies, determining campaign targets, and selecting appropriate communication media. The taking action and communicating stage was implemented through socialization activities, parenting education, and the use of social media to disseminate information. Meanwhile, the evaluating stage assessed program achievements, community participation, and behavioral changes among fathers within the family. This study concludes that the public relations campaign management through the GATI program has been implemented systematically and effectively in increasing fathers’ awareness of their role in parenting. This improvement is reflected in the increased involvement of fathers in children’s education, family communication, and attention to children's health and development.